"Tree‐Trunk" Design for Flexible Quasi‐Solid‐State Electrolytes with Hierarchical Ion‐Channels Enabling Ultralong‐Life Lithium‐Metal Batteries. Issue 44 (3rd October 2022) - Zheng, Yun; Yang, Na; Gao, Rui; Li, Zhaoqiang; Dou, Haozhen; Li, Gaoran; Qian, Lanting; Deng, Yaping; Liang, Jiequan; Yang, Leixin; Liu, Yizhou; Ma, Qianyi; et al.
Abstract: The construction of robust (quasi)‐solid‐state electrolyte (SSE) for flexible lithium‐metal batteries is desirable but extremely challenging. Herein, a novel, flexible, and robust quasi‐solid‐state electrolyte (QSSE) with a "tree‐trunk" design is reported for ultralong‐life lithium‐metal batteries (LMBs). An in‐situ‐grown metal–organic framework (MOF) layer covers the cellulose‐based framework to form hierarchical ion‐channels, enabling rapid ionic transfer kinetics and excellent durability. A conductivity of 1.36 × 10 −3 S cm −1, a transference number of 0.72, an electrochemical window of 5.26 V, and a good rate performance are achieved. The flexible LMBs fabricated with as‐designed QSSEs deliver areal capacity of up to 3.1 mAh cm −2 at the initial cycle with high mass loading of 14.8 mg cm −2 in Li‐NCM811 cells and can retain ≈80% capacity retention after 300 cycles. An ultralong‐life of 3000 cycles (6000 h) is also achieved in Li‐LiFePO4 cells. This work presents a promising route in constructing a flexible QSSE toward ultralong‐life LMBs, and also provides a design rationale for material and structure development in the area of energy storage and conversion. Abstract : A flexible and robust quasi‐solid‐state electrolyte (QSSE) with a "tree‐trunk" structure is designed for ultralong‐life lithium‐metal batteries, in which an in‐situ‐grown metal–organic framework (MOF) layer covers the cellulose‐based framework to form hierarchical ion‐channels, enabling rapid ionic transfer kinetics and excellent durability.